Preclinical and Phase I Results of Decitabine in Combination with Midostaurin (PKC412) for Newly Diagnosed Elderly or Relapsed/Refractory Adult Patients with Acute Myeloid Leukemia. Issue 12 (24th June 2013) - Williams, Casey B.; Kambhampati, Suman; Fiskus, Warren; Wick, Jo; Dutreix, Catherine; Ganguly, Siddartha; Aljitawi, Omar; Reyes, Ruben; Fleming, Allan; Abhyankar, Sunil; Bhalla, Kapil N.; McGuirk, Joseph P.
<x xml:space="preserve">Abstract</x> Purpose To determine the preclinical activity, clinical maximum tolerated dose (MTD), and recommended phase II dose of midostaurin (MS) combined either sequentially or concurrently with intravenous decitabine (DAC) in newly diagnosed patients 60 years or older or relapsed/refractory adult patients (18 years or older) with acute myeloid leukemia (AML). Patients and Methods Cultured and primary AML cells were treated with DAC and/or MS and analyzed by flow cytometry and immunoblot analyses. In the phase I study, 16 patients were enrolled; 8 were newly diagnosed patients 60 years or older and 8 were 18 years or older with relapsed AML. Only 2 of 16 patients (13%) had FLT3‐internal tandem duplication (ITD) mutations, and no patient had KIT mutations. Results Compared with treatment with either agent alone, sequential treatment with DAC and MS exerted superior anti‐AML activity in cultured and primary FLT3‐ITD–expressing AML cells. In the subsequent phase I study, the MTD and schedule of administration of the combination was identified as DAC followed by MS. Three patients developed dose‐limiting toxicities: two patients developed pulmonary edema requiring mechanical ventilation and one patient developed a prolonged QTc greater than 500 msec. Based on an intent‐to‐treat analysis, 57% of the patients achieved stable disease or better while enrolled in the trial; 25% had a complete hematologic response. Pharmacokinetic analysis revealed results similar to those previously reported for MS. Conclusion The in vitro combination of DAC and MS is synergistically active against FLT3‐ITD mutations expressing AML cells. In a clinical setting, the combination of sequentially administered DAC followed by MS is possible without significant unexpected toxicity, but the concurrent administration of DAC and MS led to pulmonary toxicity after only a few doses. On the basis of these results, additional studies exploring the sequential combination of untreated AML in elderly patients are warranted to further evaluate this combination at the MTD.